The effect of the implementation of the literacy movement on the reading ability of V grade students at Sokoharjo elementary school - Chisa Amanda Putri; Nur Ngazizah; Rintis Rizkia Pangestika (Inovasi Kurikulum, 2025)
The literacy movement at Sokoharjo Elementary School is implemented through a reading corner program, flashcards, and biographical texts of heroes, designed to create an engaging reading environment for students. Gerakan Literasi Sekolah (GLS), with its reading corner, offers access to a diverse range of reading materials. GLS utilizes flashcards to improve vocabulary recognition and quick comprehension. Additionally, the literacy movement with biographical texts of heroes enriches general knowledge and motivates students through inspirational stories. This study aims to measure the effect of the literacy movement program on the reading ability of fifth-grade students at Sokoharjo Elementary School. A quantitative approach, utilizing an experimental design, was employed in this study. To measure its effect, a Paired Sample T-Test statistical test was used, which showed a substantial average difference between the results of the initial test (pre-test) and the final test (post-test) of students. These findings demonstrate that the literacy movement has been successful in enhancing the reading abilities of fifth-grade students at Sokoharjo Elementary School. Thus, the literacy movement can be recognized as an effective method for improving students' reading abilities.   Abstrak Gerakan literasi di SDN Sokoharjo diimplementasikan melalui program pojok baca, flash card, dan teks biografi pahlawan yang dirancang untuk menciptakan lingkungan membaca yang menarik bagi peserta didik. Gerakan Literasi Sekolah (GLS) dengan pojok baca menyediakan akses ke beragam bahan bacaan, gerakan literasi menggunakan flash card untuk meningkatkan pengenalan kosakata dan pemahaman cepat, serta GLS dengan teks biografi pahlawan memperkaya pengetahuan umum dan memotivasi peserta didik melalui kisah inspiratif. Penelitian ini bertujuan untuk mengukur pengaruh program gerakan literasi terhadap kemampuan membaca peserta didik kelas V SDN Sokoharjo. Pendekatan kuantitatif dengan desain eksperimen digunakan dalam penelitian ini. Untuk mengukur pengaruhnya, digunakan uji statistik Paired Sample T-Test yang menunjukan perbedaan rata-rata yang substansial antara hasil tes awal (pre-test) dan tes akhir (post-test) peserta didik. Temuan ini membuktikan bahwa gerakan literasi berhasil meningkatkan kemampuan membaca peserta didik kelas V SDN Sokoarjo. Dengan demikian, gerakan literasi dapat diakui sebagai metode yang efektif untuk meningkatkan kemampuan membaca peserta didik. Kata Kunci: biografi; gerakan literasi; kemampuan membaca